2014
DOI: 10.1097/ncq.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Provider Coordination on Nurse and Physician Perceptions of Patient Care Quality

Abstract: The objective of this study was to assess the role of provider coordination on nurse manager and physician perceptions of care quality, while controlling for organizational factors. Findings indicated that nurse-nurse coordination was positively associated with nurse manager perceptions of care quality; neither physician-physician nor physician-nurse coordination was associated with physician perceptions. Organizational factors associated with positive perceptions of care quality included facility support of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…Additionally, the findings of the study are consistent with the results of previous studies discussing the impact of the structured NLR and nurse leader practices on enhancing the coordination of care and the discharge process (Alaloul, Williams, Myers, Jones, & Logsdon, ; McIntosh et al, ). A structured NLR is an opportunity for the nurse manager to ensure that all discharge instructions, education, and coordination of care after discharge are in place before discharge (Eggenberger, Garrison, Hilton, & Giovengo, ; Page et al, ; Sharma et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the findings of the study are consistent with the results of previous studies discussing the impact of the structured NLR and nurse leader practices on enhancing the coordination of care and the discharge process (Alaloul, Williams, Myers, Jones, & Logsdon, ; McIntosh et al, ). A structured NLR is an opportunity for the nurse manager to ensure that all discharge instructions, education, and coordination of care after discharge are in place before discharge (Eggenberger, Garrison, Hilton, & Giovengo, ; Page et al, ; Sharma et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…For example, in the airline industry, relational coordination across 12 workgroups was associated with quality outcomes such as fewer passenger complaints, fewer late arrivals, and fewer baggage handling errors (Gittell, 2001). Similarly, subsequent studies in health care found relational coordination among interdisciplinary staff was positively associated with quality outcomes such as postoperative functional status, patient-reported quality of care and quality of life, family satisfaction with care, patient trust and confidence in their providers, and patient psychological well-being (Azar et al, 2017;Bae et al, 2010;Cramm et al, 2014;Cramm & Nieboer, 2012a, 2014aDeJesus, 2015;Gittell, 2002a;Gittell et al, 2000;Gittell et al, 2008;Havens et al, 2010;Noël et al, 2013;Romanow et al, 2018;Sakai et al, 2015;Sakai et al, 2016;Weinberg et al, 2007) as well as staff-reported quality of care (McDermott et al, 2017;McIntosh et al, 2014). These findings were further replicated in studies conducted in the pharmacy, professional services, higher education, and elder care industries (Alvarez, 2014;Drewery et al, 2016;Gittell et al, 2008;Hoos et al, 2012;Margalina et al, 2017;Skakon, 2014).…”
Section: Quality Outcomesmentioning
confidence: 95%
“…Relational coordination among nurses in inpatient settings has also been found to be positively associated with nurse-rated quality of care (McIntosh et al, 2014). Other studies have also generally found positive associations between RC and quality of care (Cramm, & Nieboer, 2012; Noel, Lanham, Palmer, Leykhum, & Parchman, 2013; Hartgerink, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%